Efficient utilization of adaptive LMS channel estimation with activity detection guidance and tap decoupling in indoor optical wireless communication systems - Hammad, Randa S.; El-Rabaie, El-Sayed M.; El-Bendary, Mohsen A. M.; El-Hag, Noha A.; El-Samie, Fathi E. Abd; Al-Hanafy, Waleed (Journal of optics (New Delhi), 2024)
The diffuse indoor links in Optical Wireless Communication (OWC) suffer from Inter-Symbol Interference (ISI). This interference limits the maximum achievable data rate, and results in additional power penalty. The main reason for ISI is not only multipath propagation but also the correlation existing in the input optical signal. The correlated input signal may cause tap coupling in the estimated channel impulse response and lead to ISI, which is difficult to mitigate with standard equalizers. In this paper, an adaptive Least Mean Square (LMS) algorithm with Activity Detection Guidance (ADG) and Tap Decoupling (TD) is used at the receiver side for channel estimation in order to mitigate the problem of ISI through channel equalization. The performance of the proposed adaptive channel estimator is compared with that of an adaptive estimator that depends on the standard LMS algorithm. The OOK-NRZ modulation technique is adopted, because it is one of the most commercially used modulation techniques due to its easy implementation and bandwidth efficiency. The simulation results reveal that the adaptive LMS channel estimator with ADG and TD can mitigate the ISI problem and estimate the channel impulse response, effectively.